The influence of some environmental factors on cytological and biometric parameters and chlorophyll content of Deschampsia antarctica Desv. in the maritime Antarctic - Parnikoza, I.Yu.; Loro, P.; Miryuta, N.Yu.; Kunakh, V.A.; Kozeretska, I.A. (Цитология и генетика, 2011)
Under the environmental conditions of the Point Thomas Oasis (King George Island, the South Shetland Islands), we studied the influence of month-long artificial treatment with fresh water, salt water, and guano solution on the biometric characteristics, chlorophyll content, as well as the nuclear area of leaf parenchymal cells and nuclear DNA content, in a maritime Antarctic aboriginal plant Deschampsia antarctica. The modeled factors induced an increase in the generative shoot height and the length of the largest leaf, but did not influence the number of flowers. Treatment with guano caused an increase in the chlorophyll a and b contents, while fresh water treatment only led to some increase in chlorophyll a. Fluctuations of physiologically significant traits, such as the nuclear area and DNA content in the leaf parenchyma cells of D. antarctica, have been traced under the influence of the studied factors. Understanding of the hierarchy of influence of these factors as well as and sensitivity of plants of this species to external agents require further investigation.